Adaptation and Stuttering - MG, Kalai Selvan (Journal of All India Institute of Speech and Hearing)
Stuttering remains still a mystery. In this area, in spite of extensive research, questions outnumber the answers. Many of the theories of stuttering have emerged from the field of Psychology. Many explanations are made regarding stuttering behaviour. Adaptation is one such phenomenon. For the first time, Van Riper and Hull (1935) observed the phenomenon. Johnson and Knott (1937) attempted to measure it. Eisenson and Horowitz (1945) reported decrease in stuttering with the reduction of meaning in the material. Newman (1954) found it to be present less in self-formulated speech, than in oral reading. Shulman (1955) studied increase of audience and adaptation. Peins (1961), Brenner, et al (1972) found it as being due to rehearsal of reading material. Donhue (1955) found less decrease in stuttering on continuously changing the reading material. Newman (1963) found contrary evidence. Wingate (1966) rejected the impli- cations.